Anti-diabetic Effect of Ethanol Leaf Extract of Ziziphusspina-christi on Alloxan Induced Albino Rats (Lafia Journal of Scientific and Industrial Research, 2024)
This study aimed to evaluate the impact of an ethanol extract obtained from the leaves of Ziziphus spina christi on alloxan-induced diabetic rats using standard analytical procedures. Fifteen Albino Wistar rats were divided into five groups, each consisting of three rats. The groups included a normal uninduced rats as control group, a diabetic untreated group as the diabetic control, a group treated with a dosage of 150mg/kg body weight, a diabetic group treated with metformin as the standard drug, and another treatment group. The levels of liver marker enzymes, such as alanine transaminase (60.7±3.25) and aspartate transaminase (69.5±1.84), as well as liver function parameters like total protein (7.47±0.02), were found to be higher in the diabetic control group compared to the normal control and other treatment groups. However, in all the treatment groups, there was a significant decrease observed in alanine transaminase, aspartate transaminase, and alkaline phosphatase. The level of kidney function markers such as blood creatinine (1.58±0.07) and blood urea (43.50±0.86) were significantly (p˃0.05) higher in the diabetic control group when compared to the normal control. However, significant (p˃0.05) reductions in blood creatinine and blood urea were observed in all the treatment groups. The presence of phytochemicals such as alkaloids, tannins, flavonoids, phenols, and cardiac glycosides in the ethanolic extract of sidr leaves were probably responsible for the anti-diabetic activities of the plant extract. In conclusion, the antidiabetic effect of ethanolic extract of sidr as observed in this study may be attributed to its antioxidant properties.